2011
DOI: 10.1177/0022219411400019
|View full text |Cite
|
Sign up to set email alerts
|

On the Importance of a Cognitive Processing Perspective: An Introduction

Abstract: Children with learning problems require early intervention. If it is evidence based and implemented with integrity and intensity, it will accelerate the academic progress of many students. This is the hope and expectation of the many supporters of responsiveness-to-intervention (RTI). A minority of children, however, will not respond sufficiently to such intervention because of learning disorders like specific learning disabilities (SLD). Some RTI models do not include research-backed methods to identify these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Multiple investigations have reported that broad cognitive abilities have direct effects on reading and math achievement beyond the general factor (Benson, 2008; Floyd, Keith, Taub, & McGrew, 2007; Hajovsky et al, 2014; Taub, Keith, Floyd, & McGrew, 2008; Vanderwood, McGrew, Flanagan, & Keith, 2001), but the predictive effects associated with those abilities are relatively small (Beaujean, Parkin, & Parker, 2014; Glutting, Watkins, Konold, & McDermott, 2006; Oh, Glutting, Watkins, Youngstrom, & McDermott, 2004; Parkin & Beaujean, 2012). Whereas there is emerging evidence (e.g., Compton, Fuchs, Fuchs, Lambert, & Hamlett, 2012; Fuchs, Hale, & Kearns, 2011) that individuals with SLD may present with discrepant cognitive profiles when compared with normal controls, these cognitive correlates rarely mediate academic intervention outcomes (Fletcher et al, 2011; Miciak, Stuebing, et al, 2014; Stuebing et al, 2014).…”
Section: Are Psw Models Diagnostically Valid?mentioning
confidence: 99%
“…Multiple investigations have reported that broad cognitive abilities have direct effects on reading and math achievement beyond the general factor (Benson, 2008; Floyd, Keith, Taub, & McGrew, 2007; Hajovsky et al, 2014; Taub, Keith, Floyd, & McGrew, 2008; Vanderwood, McGrew, Flanagan, & Keith, 2001), but the predictive effects associated with those abilities are relatively small (Beaujean, Parkin, & Parker, 2014; Glutting, Watkins, Konold, & McDermott, 2006; Oh, Glutting, Watkins, Youngstrom, & McDermott, 2004; Parkin & Beaujean, 2012). Whereas there is emerging evidence (e.g., Compton, Fuchs, Fuchs, Lambert, & Hamlett, 2012; Fuchs, Hale, & Kearns, 2011) that individuals with SLD may present with discrepant cognitive profiles when compared with normal controls, these cognitive correlates rarely mediate academic intervention outcomes (Fletcher et al, 2011; Miciak, Stuebing, et al, 2014; Stuebing et al, 2014).…”
Section: Are Psw Models Diagnostically Valid?mentioning
confidence: 99%
“…In contrast, others observe the general lack of evidence that patterns of strengths and weaknesses in cognitive attributes interact with treatment outcomes (Fuchs, Hale, & Kearns, 2011;Kearns & Fuchs, 2013;Pashler, McDaniel, Rohrer, & Bjork, 2009). Kearns and Fuchs (2013) reported that although cognitively focused instruction is more effective than Tier I delivered by general education teachers, cognitively focused instruction was not more effective than rigorous academically focused instruction.…”
mentioning
confidence: 99%
“…In contrast, others observe the general lack of evidence that patterns of strengths and weaknesses in cognitive attributes interact with treatment outcomes (Fuchs, Hale, & Kearns, 2011;Kearns & Fuchs, 2013;Pashler, McDaniel, Rohrer, & Bjork, 2009). Kearns and Fuchs (2013) reported that although cognitively focused instruction is more effective than Tier I delivered by general education teachers, cognitively focused instruction was not more effective than rigorous academically focused instruction. Less controversial is the evidence that specific cognitive skills can serve as precursors and predict those at risk for reading failure (Scarborough, 1998) although there is disagreement and uncertainty about what variables are most predictive.…”
mentioning
confidence: 99%
“…Research literature in cognitive science and neuropsychology is replete with evidence to support our understanding of how cognition affects achievement (e.g., Fiorello, Hale, & Wycoff, ; Flanagan, Ortiz, Alfonso, & Mascolo, ; McGrew & Wendling, ). Entire journal issues have been devoted to how cognition and individual differences influence intervention (see Fuchs, Hale, & Kearns, ). Indeed, many have already suggested that school psychologists are in a unique position to “take the lead role in the translation of brain research, cognitive neuroscience, and neuropsychological research related to neurodevelopmental disabilities into educational practice” (Maricle, Miller, Hale, & Johnson, , p. 78; see also Decker, 2008; Flanagan & Alfonso, ; Flanagan & Harrison, ; Fletcher‐Janzen & Reynolds, ; Hale & Fiorello, ; Miller, ).…”
Section: Cognitive Assessment Is Not Synonymous With Iq Testingmentioning
confidence: 99%
“…Administering specific narrowly defined cognitive tasks helps to systematically isolate the underlying problem. The purpose of administering the tests is not to get an IQ score, but to help understand learning problems (Woodcock, ) and develop effective interventions (Fuchs et al., ). This is an important distinction from viewing testing for the purpose of predicting achievement (Glutting, Watkins, Konold, & McDermott, 2006; Watkins, Lei, & Canivez, ).…”
Section: Cognitive Assessment Is Not Synonymous With Iq Testingmentioning
confidence: 99%